1994
DOI: 10.1046/j.1471-4159.1994.63062058.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Is Expressed in Different Types of Glial Cells in Culture

Abstract: Estrogens derived from the aromatization of androgens are believed to be responsible for the induction of the sexual differentiation of the CNS interacting with specific estrogen receptors (ER) present in developing neurons . However, the brain cellular distribution of ER is not so well documented . The aim of this study was to investigate the qualitative and quantitative expression of ER mRNA in well characterized cultures of rat type 1 and type 2 astrocytes and of oligodendrocytes by polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(74 citation statements)
references
References 13 publications
6
68
0
Order By: Relevance
“…This cell type has the greatest potential for a critical role in steroid-mediated protection of neurons in the brain, since ablation of astrocytes in vivo results in a significant decrease in neuronal survival (Cui et al 2001). Indeed, astrocytes are well-described target cells for E and P expressing the corresponding nuclear steroid receptors (Jung Testas et al 1992, Santagati et al 1994, Beyer 1999, Quadros et al 2007. Confirming previously published data (Pawlak et al 2005), we observed transcripts for ERa, ERb, and PR in cortical astrocytes from both genders.…”
Section: Discussionsupporting
confidence: 88%
“…This cell type has the greatest potential for a critical role in steroid-mediated protection of neurons in the brain, since ablation of astrocytes in vivo results in a significant decrease in neuronal survival (Cui et al 2001). Indeed, astrocytes are well-described target cells for E and P expressing the corresponding nuclear steroid receptors (Jung Testas et al 1992, Santagati et al 1994, Beyer 1999, Quadros et al 2007. Confirming previously published data (Pawlak et al 2005), we observed transcripts for ERa, ERb, and PR in cortical astrocytes from both genders.…”
Section: Discussionsupporting
confidence: 88%
“…Oestrogen receptors present in primary glial cell cultures and different types of glial cells (Jung-Testas et al, 1992;Santagati et al, 1994;Yague et al, 2004) allow this non-neuronal cells of the CNS to respond to oestrogens; so glioma cells were able to respond significantly to oestradiol in the culture. Melatonin, only at 1 mM concentration, counteracted the growth stimulatory effect of oestradiol on C6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…E 2 alters many aspects of hippocampal morphology, including synapse number, spine density, and astrocytic volume (50)(51)(52). In brain, astrocytes contain ER␤ (53,54). Moreover, ER␤KO brains display fewer Nissl-stained neurons and increased glial fibrillary acidic protein immunoreactive cells in the medial amygdala and preoptic area, as compared with WT littermates (55).…”
Section: Discussionmentioning
confidence: 99%